PENGARUH KONFLIK PERAN, KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEMERIKSA PAJAK PADA KPP MADYA PEKANBARU DAN KPP MADYA BATAM - Sholihin Sholihin; Enni Savitri; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research aimed to analyse the effect role conflict, work satisfaction and organizational of cultural to performance of tax auditors at KPP Madya Pekanbaru and KPP Madya Batam. The respondent from this research are auditors that working at KPP Madya Pekanbaru and KPP Madya Batam. The samples with saturated sample method. The data used are primary data collected through questionnaires. Questionnaires which can be processed is number 52 questionnaires from 65 questionnaires distributed. Data analysis techniques using multiple regression analysis using SPSS version 20 was used to test whether the independent variables affect the dependent variable. Results of this study indicate that role conflict, work satisfaction and organizational culture influence on the performance of tax auditors in the KPP Madya Pekanbaru and KPP Madya Batam.Keywords: Performance of Tax Auditors, Role Conflict, Work Satisfaction, and Organization of Cultural.